Bioinorganics and Wound Healing. Issue 18 (12th August 2019) - Dalisson, Benjamin; Barralet, Jake
Abstract: Wound dressings and the healing enhancement (increasing healing speed and quality) are two components of wound care that lead to a proper healing. Wound care today consists mostly of providing an optimal environment by removing waste and necrotic tissues from a wound, preventing infections, and keeping the wounds adequately moist. This is however often not enough to re‐establish the healing process in chronic wounds; with the local disruption of vascularization, the local environment is lacking oxygen, nutrients, and has a modified ionic and molecular concentration which limits the healing process. This disruption may affect cellular ionic pumps, energy production, chemotaxis, etc., and will affect the healing process. Biomaterials for wound healing range from simple absorbents to sophisticated bioactive delivery vehicles. Often placing a material in or on a wound can change multiple parameters such as pH, ionic concentration, and osmolarity, and it can be challenging to pinpoint key mechanism of action. This article reviews the literature of several inorganic ions and molecules and their potential effects on the different wound healing phases and their use in new wound dressings. Abstract : The literature concerning the reported effects of several inorganic ions and molecules and on the different wound healing phases is reviewed to better understand their beneficial biological effects and how they can be used in new wound dressings and biomaterials to enhance healing speed and quality.